Personality disorder co‐morbidity in primary care 'Improving Access to Psychological Therapy' services: A qualitative study exploring professionals' perspectives of working with this patient group. (24th June 2019) - Lamph, Gary; Baker, John; Dickinson, Tommy; Lovell, Karina
Abstract: A high prevalence of people present to 'Improving Access to Psychological Therapies' (IAPT) in England with common mental health disorders and co‐morbid personality disorder. This group have suboptimal treatment outcomes in IAPT. Whilst new short‐term treatment approaches are advocated, no solutions or guidance have been provided. This qualitative study explored IAPT health‐care professional ( N = 28) perspectives of working with people who present to IAPT with co‐morbid personality disorder. Individual semi‐structured interviews were digitally recorded, transcribed verbatim and analysed using a framework analysis approach. Results identified a lack of skills and confidence in working with this patient group, restrictive service constraints and a treatment gap between the interface of primary and secondary services. Insight into acceptable adaptions to practice are identified that have transferable utility to a wider international audience who can identify people outside of specialist mental health services with common mental health disorders and co‐morbid personality disorder traits. © 2019 John Wiley & Sons, Ltd.